Strategies for learning second language skills: Arabic speaking skills in the Malaysian context - El-Tingari, Salih (International Journal of English Language Teaching and Linguistics, 2016)
The article is entitled “Second Language Strategies: Arabic Speaking as a Model.” The aim of article to answer 2 questions: 1. What the strategies of speaking skill? 2. What the strategies adopted by Malaysian learners? Speaking skill is a complicated skill which requires four steps: A. stimulation B. thinking C. formulation D. speech. In addition to the above, speaking is a reaction between two or more people (speaker – listener). Considering this four steps, we can imagine the difficulties and obstacles faced by second language learner, e.g anxiety, fear, loss of confidence, the negative effect of first language and the difference in the sound system from writing system, special in Arabic. The field of learning foreign language manged to overcome a lot of problems that has to do with the teaching and learning a second language. One of newest issues is the concept of learning strategies. The study depends on Rebecca Oxford (Strategy Inventory for Language Learning (SILL, Version 5.1). One of the methodologies used in carrying the research was questionnaire contants the direct strategies. The sample of study is 20 students, 3 males (15%), 17 females (85%), all of them are Malaysians study in IIUM. The research found out the use of the direct strategies (compensation, memory, cognitive) among the study sample is either average or high. In addition the strategies used by the sample appeared in the following form: A. Compensation strategies, B. Memory strategies and C.Cognitive strategies.